Planning of urban green areas of Štip - Despot, Katerina; Sandeva, Vaska; Simovski, Bojan; Acevski, Jane (Ss. Cyril and Methodius University in Skopje, Faculty of Forestry in Skopje, 2013)
The setup structure of functions for holiday and recreation in spare time of the citizens is a great worth. The needs of the urban population for rest and recreation are becoming larger, thus increasing the need for design and planning of green spaces (parks, gardens, etc.) not only in cities but also in their immediate environment. In many cities around the world for centuries been paid great attention to this area. In this paper we try to present the main processes in the planning of urban recreational areas of emphasis of the Municipality of Štip.
Professional article
Keywords: city; recreation; park; garden; planning; Štip